O “eu” e o “outro”: as imagens da afetividade nas obras de Lília A. Pereira da Silva - Evangelista, Job Lopes (2018)
This research first presents characteristics, themes and possibilities of study in relation to the works of the writer Lília Aparecida Pereira da Silva: contemporary author of the Brazilian Literature with little academic study. The present thesis consists of the comparative and interpretative study of the present thesis consisting in the comparative and interpretative study of the affective images that are constructed from the human relations between the "I" and the "Other‖, the anguish, the unhappiness, the lack of love and the existential void, that are developed in three aesthetics: poetry , dramaturgy and drawing. The objective of this study is not to analyze the genres covered, but how these images are configured in them. From this point on, existential relations develop affective reactions, perceptions and images that become constant in the writer's productions. The study investigates these relations in ten poems in the works. Three years of poetry volumes I and II: Statue (1991), Constant (1991), Metamorphosis (1991), I accept becase (1991), Rose of masks (1991), Psalm of loneliness(1991), Empty cage 1991), Self-portrait (1991), Sixteen (1991) and Sixty-one (1991). An anguished and melancholic lyrical self presents in all the poems analyzed, by the presence of the "Other", by its absence. In this sense, the book A jew in my bed (1997), presents the relations between the "I" and the "Other" shaped by the characters Gad and Luana, who experience the affective sufferings and the existential questionings. From the works Carnival Brazil (1996) and Drawings for Pedrinho (2001), six colorless drawings are analyzed, in which duplicity is in the inner relation of the "I" with it. Using a literary, psychoanalytical: Sigmund Freud; Jacques Lacan; Carl Gustav Jung and Otto Rank and philosophical:Sören Kierkegaard; Jean Paul-Sartre; Arthur Schopenhauer and Luiz Costa Lima, theoretical framework, the thesis presents the affective images that are transgressed from human relations in the works of Lília A. Pereira da Silva.